Impediments to the effectiveness of monetary policy in Suriname - Adhin, Rakesh ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1999)
Deals with the inflationary impact of wage and fiscal policy in Suriname during 1990-1998.